Dear Lisa, - Peh, Lisa Jiaxian (Nanyang Technological University, 2022)
Dear Lisa, is an open letter to my past, present and future self. Built upon my experiences in the Singapore education system, I revisit its role in promoting individuality within the constraints of a collective identity. I relook at how I navigated through themes of conformity, obedience and self within these confines. Through the process, I gained newfound insights into my inner being and what it means to break away from the mould of fulfilling external expectations.